Evaluation of Dimensional Accuracy and Surface Topography of Plastic Parts - Jurickova, Eva; Kolomy, Stepan; Sedlak, Josef; Hrusecka, Denisa; Sliwkova, Petra; Vitek, Jiri (Manufacturing Technology Journal, 2025)
The objective of this paper is the evaluation of dimensional and geometric accuracy and surface to-pography of milled parts from plastic. This evaluation was done on 10 samples from various thermo-plastics made by extrusion and FDM 3D printing. The samples were then milled. One side was milled dry while the other was milled with cutting fluid, which has improved the texture of the result-ing machined surfaces in most cases, for example with printed PLA, where Ra was reduced by 1.8 um. For determining the dimensional and geometric accuracy, two parameters were chosen, those being distance and parallelism. For evaluating the surface topography, 4 parameters were measured using 2D profile roughness and 3D surface texture. The surface of the prints was greatly improved by machining. The paper ends with practical recommendations for choosing different plastic materials for applications, requiring high dimensional accuracy and low surface roughness.
Keywords: Extrusion; Machining; Plastic; Dimension; 3D printing